Elastically induced phase-shift and birefringence in optical fibers [version 1; peer review: 1 approved, 2 approved with reservations] - Piotr T. Chruściel; Elisabeth Steininger; Thomas Mieling (Open Research Europe)
Background Light propagation in optical fibers is known to be sensitive to ambient conditions such as changes in temperature and pressure. Building on a model for elastic deformations of optical fiber spools derived in previous work, the induced effects on phase and birefringence are investigated. Methods We use a perturbative scheme to solve, to first order, the Maxwell equations in deformed and anisotropic fibers using a multiple-scales approximation scheme. Specifically, we consider differences in wave-guiding properties of straight fibers subject to different external temperatures, pressures, and gravitational fields. Results We obtain propagation equations for the Jones vector along optical fibers. This results in phase shifts and birefringence effects, for which we derive explicit expressions. Conclusions The phase shift can be expressed in terms of the average radial pressure, longitudinal tension, and change in temperature, while birefringence depends on the quadrupole of the external pressure distribution and the stresses on the axis of the fiber. Our result provides stringent constraints on the environmental control needed for sensitive fiber interferometry.